Fluctuating tourism patterns : SME’s adaptive strategies in Nairobi - Njamiu, Daisy; Chiawo, David (Strathmore University, 2014)
Tourism seasonality has been well reviewed in available literature. However, research on effects of seasonality on Small Medium Enterprises (SMEs) has been limited, especially in East Africa. This study sought to investigate on fluctuating tourism patterns and possible effects on tourism SMEs in Nairobi area. We examined coping strategies applied by SMEs to the fluctuating patterns. We analysesd primary data from 80 SMEs and additional cases from available database. Tourism off-peaks showed significant impact on tourism SMEs with near 100% of surveyed groups indicating significant effect. Among the strategies applied to cope with the tourism fluctuating patterns included; cooperation with other SMEs, marketing, promotions and discounts. Product diversification and innovations appeared to be major coping strategies with significant socio-economic returns among SMEs. Despite the need for such adaptive strategies, some SMEs had none in place and had limited consciousness to such fluctuating tourism patterns with negative economic impacts to their businesses. There is need for intervention of major tourism stakeholders including, Government, established tourism enterprises, tourism product developers and marketing agencies to improve innovation and entrepreneurship among the small holder tourism businesses. Having a wide range of strategies to deal with the effects of tourism seasonality showed viable economic gains and competitive advantage.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: SME's; Strategy; Tourism